Studies in Contract Law of Asia: Contents of Contracts and Unfair Terms - Hinz, Julian (Zeitschrift für Japanisches Recht, 2021)
Hosted online by the Max Planck Institute for Comparative and International Private Law, Hamburg, 8 December 2020